Edukasi Hukum dan Literasi Digital Generasi Z: Pendekatan Interaktif Melawan Kekerasan Seksual di Era Kecerdasan Buatan di SMA Negeri 1 Wangon - Ruhtiani, Maya; Tri Naili, Yuris; Candrawijayaning Fajri, Pujangga; Fitria Rahmawati, Apitta (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This community engagement article aims to enhance the legal awareness and digital literacy of students at SMA Negeri 1 Wangon in addressing the growing phenomenon of sexual violence in digital spaces, particularly in the era of artificial intelligence. The primary issue faced by Generation Z today is a lack of legal understanding and weak digital ethics, which makes them vulnerable to becoming both victims and perpetrators of online sexual violence. The program employed a participatory approach using methods such as observation, group discussions, case simulations, and evaluation through pre- and post-tests. The results indicate that the legal and digital literacy education program significantly improved participants’ understanding of legal frameworks, including the Law on Sexual Violence Crimes (UU TPKS) and the Electronic Information and Transactions Law (UU ITE). The program also fostered awareness of digital ethics and the importance of personal data security. The implementation process revealed high levels of enthusiasm among students, particularly during the creation of anti-sexual violence digital campaigns, which were later published on the school's social media platforms. This program had a positive impact on students’ ability to recognize, prevent, and respond to digital sexual violence, while also encouraging the formation of a legally conscious student community that can serve as a driving force for digital cultural transformation within the school environment.